O impacto do dashboard no gerenciamento de dados pedagógicos no cotidiano escolar - Silva, Cristiane Gomes da (2025)
This present research is based on the premise that technology is widely present in people’s daily lives, influencing various aspects of social life. However, some public institutions still face challenges in adopting technological innovations. This scenario is evident in the municipality of Santa Rita, particularly at Escola Municipal Vovó Vina, where the management of pedagogical data is still conducted manually, compromising efficiency and decision-making. Given this issue, the following research question was formulated: What is the impact of the dashboard on the management of pedagogical data in the daily school routine at Escola Municipal Vovó Vina? To answer this question, the study aimed to analyze the effects of implementing this tool in the pedagogical management of the school. The research adopted the Design Science Research method, structured in six stages, from problem identification to the communication of results. As a technological artifact, GestEduc was developed—an intuitive dashboard that synthesizes pedagogical data, facilitating the analysis and interpretation of educational indicators. The tool's evaluation was conducted through semi-structured interviews with teachers and school administrators. The results indicated that the use of the dashboard brought significant benefits to school management, as reported by the participants. Among the advantages highlighted were ease of use, the ability to interpret data such as school attendance, academic performance, and age/grade distortion, as well as the identification of problems and the formulation of more effective pedagogical strategies. The tool was well received and considered an innovative resource for modernizing educational management. In conclusion, the implementation of the dashboard contributes to a more dynamic and efficient teaching process, enabling informed decision-making in a timely manner.